2018
DOI: 10.1073/pnas.1716661115
|View full text |Cite
|
Sign up to set email alerts
|

Structure and function of the archaeal response regulator CheY

Abstract: Motility is a central feature of many microorganisms and provides an efficient strategy to respond to environmental changes. Bacteria and archaea have developed fundamentally different rotary motors enabling their motility, termed flagellum and archaellum, respectively. Bacterial motility along chemical gradients, called chemotaxis, critically relies on the response regulator CheY, which, when phosphorylated, inverses the rotational direction of the flagellum via a switch complex at the base of the motor. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
71
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(74 citation statements)
references
References 84 publications
1
71
0
Order By: Relevance
“…Corresponding with this hypothesis, an interactome study in Halobacterium salinarum, previously indicated that ArlCE (fused in this organism) interacts with the archaeal specific chemotaxis protein CheF (Figure 1a) (Schlesner et al, 2009;Schlesner et al, 2012). Motile archaea encoding the bacterial-like chemotaxis system, all possess the adaptor protein CheF, which can bind to CheY and as such forms a link between the chemotaxis system and the archaellum (Schlesner et al, 2009;Quax et al, 2018b).…”
Section: Introductionmentioning
confidence: 65%
“…Corresponding with this hypothesis, an interactome study in Halobacterium salinarum, previously indicated that ArlCE (fused in this organism) interacts with the archaeal specific chemotaxis protein CheF (Figure 1a) (Schlesner et al, 2009;Schlesner et al, 2012). Motile archaea encoding the bacterial-like chemotaxis system, all possess the adaptor protein CheF, which can bind to CheY and as such forms a link between the chemotaxis system and the archaellum (Schlesner et al, 2009;Quax et al, 2018b).…”
Section: Introductionmentioning
confidence: 65%
“…Cells were serially diluted and observed at early log-phase. H. volcanii wild type cells are motile and rod-shaped in early log phase and round and non-motile in stationary phase 44,46 . The majority of observed cells of the wild-type performed a random walk in the absence of directional stimuli, as has been observed before 46 (Movie S8).…”
Section: Mind4 Influences Cellular Positioning Of Motility and Chemotmentioning
confidence: 99%
“…Haloferax volcanii was grown and genetically manipulated as described in 46,69 . Depending on the experiment, the cells were grown at 45 °C or 42 °C in either rich YPC medium with Bacto TM yeast extract, peptone (Oxoid, UK) and Bacto TM Casamino acids (BD Biosciences, UK or Oxoid) or in selective CA medium containing only Bacto TM casamino acids 46,69 , occasionally supplemented with a trace elements solution as described 43 was also used where indicated (CAB medium). Plates were incubated at 45°C and liquid cultures were shaken at 120-200 rpm.…”
Section: Author Contributionsmentioning
confidence: 99%
See 2 more Smart Citations